Influence Culture Corporate Integrity towards Merger and Acquisition Performance A Review Literature and Findings Empirical - Grace Yulianti; Naya Maharani, Elga (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the influence of corporate integrity culture on merger and acquisition (M&A) performance. The study synthesizes findings from recent research, highlighting that a strong integrity culture in target firms impacts market reactions and reduces uncertainty during M&A transactions. Key mechanisms identified include the retention of directors and customers, which enhances post-acquisition stability and operational continuity. Despite the significant insights provided, this review acknowledges limitations such as reliance on secondary data and potential biases in reported corporate information. Additionally, contextual factors like industry differences and regulatory environments may affect the integrity culture-M&A performance relationship. Future research should incorporate primary data and consider these contextual variables to deepen understanding. Overall, this study underscores the critical role of cultural integrity in enhancing M&A success and offers a framework for evaluating cultural aspects in future M&A activities.